Simulasi Kekuatan Rangka Mesin Pengupas Kulit Luar Buah Pala - Bagus Suwandy; Ahmad Marabdi Siregar; Chandra A Siregar (Rekayasa Material, Manufaktur dan Energi, 2026)
Nutmeg (Myristica fragrans) is one of Indonesia's leading plantation commodities with high economic value in the food, pharmaceutical, cosmetic, and spice industries. However, the outer skin peeling process is still predominantly performed manually by small and medium-sized enterprises, resulting in low productivity, inconsistent peeling quality, and high labor intensity. Although several nutmeg peeling machines have been developed, previous studies have mainly focused on functional performance without comprehensive structural evaluation before fabrication. Consequently, the structural reliability of machine frames under operational loading remains insufficiently investigated. This study aims to design a nutmeg outer skin peeling machine capable of simultaneously peeling and separating the fruit skin from the seed while performing a numerical evaluation of the frame structure using the Finite Element Method (FEM). The machine was designed using SolidWorks 2022, followed by a linear static structural analysis employing the Finite Element Method. The simulation considered fixed boundary conditions at the frame supports and static loads of 39.2 N, 68.6 N, and 186.3 N, representing the operational loads acting on the upper frame, middle frame, and motor mounting, respectively. Structural responses were evaluated in terms of Von Mises stress, maximum displacement, and factor of safety. The numerical results showed that the maximum Von Mises stresses were 0.811 MPa, 0.751 MPa, and 5.112 MPa, respectively, while the maximum displacement reached only 1.164 mm. These values remain significantly below the material yield strength of 250 MPa, resulting in a high factor of safety of 48.9, indicating that the frame structure is mechanically safe under static loading conditions. The study demonstrates that the proposed frame design possesses sufficient structural strength and stiffness for nutmeg peeling applications. Nevertheless, the present work is limited to static numerical analysis and does not consider dynamic loading, vibration, fatigue, or weld joint behavior, which should be investigated in future studies..